Analisis Kompetensi Inti 3 (KI-3) Kurikulum 2013 pada Kelas XI SMA Berdasarkan Taksonomi Bloom Revisi - Khoirunnisah Khoirunnisah; Eka Yusmaita (Universitas Negeri Padang, 2019)
The 2013 curriculum is the latest curriculum used as a guideline for organizing learning activities to achieve educational goals. The fundamental change in the 2013 curriculum is that core competencies must be arranged in a balanced manner covering attitudes (spiritual and social), knowledge and skills. The purpose of this study is to describe the formula of KI-3 outlined based on the revised Bloom taxonomy. Taxonomy is used as one of the references in the preparation of KI-3 starting from the cognitive dimension and the lowest dimension of knowledge to the highest or complex level. This type of research is descriptive with a qualitative approach. Data collection techniques used by library research. The data source used is Permendikbud No. 37 of 2018. The formula KI-3 was analyzed based on knowledge activities, types of knowledge, and scientific attitudes. The results of the elaboration of KI-3 class XI SMA obtained 48 components of KI-3. The KI-3 component that has been described is used as a reference for the dimensions of cognitive processes and the dimensions of knowledge that must be achieved by students.